Evaluation of microbial elicitors to induce plant immunity for tomato wilt - Kasem Soytong; Chamaiporn Charoenporn; Somdej Kanokmedhakul (My University, 2013)
The bioactive compounds of Chaetoglobosin C, chaetomanone A and trichotoxin mixture used as microbial elicitors to elicit a-tomatine in tomato was investigated. The a-tomatinewas detected from tomato seedlings var. Sida sprayed with chaetoglobosin C, chaetomanone A and trichotoxin mixture, followed by the inoculation with Fusarium oxysporum f sp lycopersici. Results show that disease immunity on treated tomato seedlings with chaetoglobosin C, chaetomanone A and trichotoxin mixture at concentration 50 ug/ml after 10 days were 44.97, 35.18 and 39.43%, respectively, whileprochloraz showed disease immunity of 29.95%. The stems and leaves of tomato were extracted and spotted on TLC yielded green spot which showed Rf = 0.23 as same as a spot of standard a-tomatine. Tomato extracts were subjected into vial and analyzed for a-tomatine in HPLC system. Tomato treated with chaetoglobosin C, chaetomanone A and trichotoxin mixture at 15 days expressed a-tomatine quantity as 207.87, 254.25, and 205.04 ug/g which significantly were higher than for prochloraz and the inoculated controlwhose a-tomatine quantity were 131.56 and 77.46 ug/g, respectively. It showed that chaetoglobosin C, chaetomanone A and trichotoxin mixture could induce a-tomatine in tomato plants implying disease immunity against Fusarium wilt of tomato var. Sida through phytoalexin production. The bioactive compounds were tested for their efficacies to induce immunity in tomato wilt in vivo. The results reveal that all bioactive compounds at concentration 10, 50 and 100 µg/ml could induce plant immunity in tomato between 53.80-65.15% which significantly had higher plant disease immunity than prochloraz (26.73%) indicating that these bioactive compounds play an important role as microbial elicitors. Key words: Chaetoglobosin C, chaetomanone A trichotoxin mixture, a-tomatine, microbial elicitors, tomato wilt.
Keywords: Wilt disease; Plant-Microbe Interactions and Immunity